Pot Without Patriarchy: Gender Equity in the Adult-Use Cannabis Industry and the Feminist Cooperative Model - Koonce, Nicole (Columbia Journal of Gender and Law, 2025)
Many states that have legalized recreational cannabis in the last decade have done so with social equity in mind. So-called “cannabis social equity” programs in those states primarily aim to rectify the harms of discriminatory enforcement of cannabis laws before legalization, but they also pursue a broad vision of diversity in cannabis business ownership as the industry rapidly grows. As more data on cannabis industry demographics becomes available, states’ equity programs have received widespread criticism for their failure to realize their racial equity and restorative justice goals. There has been far less discussion of the persistent gender disparities in the cannabis industry, though. Despite states’ equity efforts, the nascency of the industry, and the fact that women are starting and leading businesses in other sectors at higher rates than ever before, women are not pulling ahead in cannabis. This Note seeks to contribute to the holistic, intersectional project of cannabis equity by exploring cannabis’s gender problem—including its causes and potential statelevel policy solutions within constitutional limits on gender-based affirmative action. It argues that women’s participation and leadership in the cannabis industry are essential in light of the hidden costs of the War on Drugs on women and women’s historic exclusion from, or exploitation by, other “vice” industries like gambling and tobacco. This Note ultimately advocates for an increased regulatory focus on support for co-op businesses, as their democratic, collective structure renders them uniquely well-suited to achieving gender equity in cannabis while prioritizing community and resisting corporate capture.